2013
DOI: 10.1186/1752-0509-7-112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of regulatory features of housekeeping and tissue-specific regulators within tissue regulatory networks

Abstract: BackgroundTranscription factors (TFs) and miRNAs are essential for the regulation of gene expression; however, the global view of human gene regulatory networks remains poorly understood. For example, how is the expression of so many genes regulated by limited cohorts of regulators and how are genes differentially expressed in different tissues despite the genetic code being the same in all tissues?ResultsWe analyzed the network properties of housekeeping and tissue-specific genes in gene regulatory networks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, miRNAs have been clustered into families constructed on seed region similarity, which is accountable for the corresponding ability to target common groups of gene transcripts [ 34 ]. Although some miRNAs exhibit a tissue-specific localization, most miRNAs show a broader tissue distribution [ 35 ]. Each miRNA can simultaneously regulate large cohorts of transcripts, and individual mRNA may include multiple binding sites for different miRNAs originating an intricate regulatory network [ 32 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs have been clustered into families constructed on seed region similarity, which is accountable for the corresponding ability to target common groups of gene transcripts [ 34 ]. Although some miRNAs exhibit a tissue-specific localization, most miRNAs show a broader tissue distribution [ 35 ]. Each miRNA can simultaneously regulate large cohorts of transcripts, and individual mRNA may include multiple binding sites for different miRNAs originating an intricate regulatory network [ 32 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have shown that miRNA function is tissue specific (see for example 12,37 ) so far no study has offered an algorithm to predict miRNA targets for a specific disease.…”
Section: Resultsmentioning
confidence: 99%
“…The good performance of the normal consensus model to classify the species-specific test sets indicates that the K nn , page rank, and degree are topological features conserved along the evolution. Notwithstanding, the good classification of GRNs from mouse embryonic stem cells also showed that these topological features arise as essential properties even before the cell differentiation, albeit a previous paper showed that the topological properties of TFs are different amongst tissues 56 , reflecting different cell states 34 .…”
Section: Discussionmentioning
confidence: 99%